Pengaruh Persepsi Kemudahan, Kepuasan, Dan Minat Pengguna Terhadap Adopsi QRIS Sebagai Inovasi Pembayaran Digital Di Kalangan Generasi Z - Elvina Hany Dennisa; Anik Malikah; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The acceleration of digital transformation has shifted public payment behavior toward cashless systems, including the Quick Response Code Indonesian Standard (QRIS). This study aims to analyze the effect of perceived ease of use, user satisfaction, and behavioral intention on QRIS adoption among Generation Z. A quantitative survey method was applied involving 100 Generation Z respondents in Malang City selected through purposive sampling. The data were analyzed using multiple linear regression with SPSS. The results reveal that perceived ease of use and user intention significantly and positively influence QRIS adoption, while user satisfaction does not show a significant effect. Simultaneously, all independent variables collectively affect QRIS adoption. The coefficient of determination (R²) of 0.326 indicates that 32.6% of QRIS adoption can be explained by the proposed variables. These findings provide insights for policymakers and service providers in formulating strategies to strengthen QRIS adoption among Generation Z. Keywords: Perceived Ease of Use; User Satisfaction; User Interest; QRIS Adoption; Generation Z